Discrimination of Dark Triad traits using the UPPS-P model of impulsivity. (1st December 2020) - Kiire, Satoru; Matsumoto, Noboru; Yoshida, Eri
Abstract: The Dark Triad personality traits–Machiavellianism, narcissism, and psychopathy–were originally defined as separate concepts sharing socially aversive qualities. Nevertheless, recent studies suggest that these personality concepts, in particular Machiavellianism and psychopathy, cannot be discriminated. In the present study, we attempt to examine whether Dark Triad traits are discriminated by the Urgency, (lack of) Premeditation, (lack of) Perseverance, Sensation Seeking, Positive Urgency (UPPS-P) model, a multidimensional model of impulsivity. We tested whether each dimension of the UPPS-P measure of impulsivity showed different associations with each Dark Triad trait. The results showed that psychopathy was positively related to all UPPS-P impulsivity dimensions while Machiavellianism was negatively related to Lack of Perseverance and Lack of Premeditation. Furthermore, narcissism was negatively associated with Lack of Perseverance and positively associated with Sensation Seeking. Thus, the present study demonstrated that Dark Triad traits can be distinguished by the UPPS-P impulsivity model. Future research investigating the relationship between Dark Triad traits and impulsivity is discussed. Highlights: Each Dark Triad trait can be distinguished using UPPS-P impulsivity. Machiavellianism was negatively related to Lack of Perseverance/Premeditation. Narcissism was positively related to Sensation Seeking. Narcissism was also negatively related to Lack of Perseverance. Psychopathy was positively related to all UPPS-P impulsivity dimensions.